Tomorrow's jobs today : wisdom and career advice from thought leaders in AI, big data, blockchain, the Internet of things, privacy and more /: wisdom and career advice from thought leaders in AI, big data, blockchain, the Internet of things, privacy and more. (2021) - Moscatel, Rafael
No abstract available